Kerjasama Orangtua dan Guru dalam Meningkatkan Motivasi Belajar Anak di Sekolah - Frasandy, Rendy; Rusdinal; Alwen Bentri; Silvia Sandi Wisuda Lubis; Dwi Nur Ummi Rahmawati (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to determine: (1) The duties and responsibilities of parents and teachers regarding students' learning motivation at school; (2) Forms of collaboration between parents and teachers in increasing students' learning motivation at school; This research is field research (Field Research) with qualitative descriptive methods. Data collection tools in this research are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research are: (1) The duties and responsibilities of parents in increasing students' learning motivation at school are almost the same as the duties and responsibilities of a teacher, only the duties and responsibilities of parents are more comprehensive than to teachers because children spend more time at home than at school. The duties and responsibilities of teachers in increasing students' learning motivation at school are as professional educators, as facilitators, as educators, as counselors, as motivators; (2) Forms of collaboration between parents and teachers are parents participating in school meetings, creating WhatsApp groups, visiting parents of students with educators.